Schrijverschap in de Belgische belle époque. Een sociaal-culturele geschiedenis - Verbruggen, Christophe (Academia Press / Vantilt, 2009)
This book studies literary sociability during the belle époque (1890-1914) by comparing and relating organizations of authors with intellectual sociability in general. Drawing on a combination of methods including social network analysis, existing histories of Dutch and French speaking literature are questioned. This study shows, for instance, how author's societies and literary journals were functional in the symbolic struggle between 'dilettante' writers on the one hand and self declared 'professional' authors on the other. It concludes that Belgian authorship was shaped within a social space that was much broader than the national social space, especially as far as the social construction of the Belgian author-intellectual was concerned. As such, being an intellectual became an important category of personal identity.